Portrait of BP3MI Riau Islands Services in the Deportation Process of Indonesian Migrant Workers in Tanjungpinang City - Richart Bonar Sirait; Novi Winarti (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study examines how the Indonesian Migrant Workers Protection Service Center (BP3MI) of the Riau Islands handles the deportation of Indonesian Migrant Workers (PMI) in Tanjungpinang City. The background of this study is the increasing number of PMI who work abroad without procedures, especially in Malaysia, which results in deportation. The study was conducted using a qualitative approach involving data collection through observation, documentation, and interviews. The results of the study indicate that BP3MI Kepri plays an important role in the process of accepting deported PMI. This includes pick-up at the port, document checking, providing basic services, and assisting in repatriation to their home areas. There are two repatriation mechanisms, the first is carried out independently and the other is fully facilitated by BP3MI. Limited shelters and the increasing number of non-procedural PMI are the problems faced. This study emphasizes the importance of the state's role in guaranteeing the rights and protection of every citizen, including PMI who have problems abroad. Therefore, BP3MI Kepri continues to coordinate across sectors to ensure comprehensive protection for PMI.